1990
DOI: 10.1002/j.1460-2075.1990.tb08166.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of FIS in trans activation of stable RNA operons of E. coli.

Abstract: The thrU(tufB) operon of Escherichia coli is endowed with a cis‐acting region upstream of the promoter, designated UAS for Upstream Activator Sequence. A protein fraction has been isolated that binds specifically to DNA fragments of the UAS, thus forming three protein‐DNA complexes corresponding to three binding sites on the UAS. It stimulates in vitro transcription of the operon by facilitating the binding of the RNA polymerase to the promoter. All three protein‐DNA complexes contain one and the same protein.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
169
1

Year Published

1991
1991
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(181 citation statements)
references
References 33 publications
11
169
1
Order By: Relevance
“…A sequence similar to the E. coli factor for inversion stimulation (FIS) binding site (22) was found at positions 299 to 308 between the -35 regions of the trmA and btuB promoters (7 of 9 bp). FIS binding sites have also been found in the rrn promoters and are centered there at about -71, i.e., somewhat further upstream than the putative FIS binding site in the trmA promoter, which is centered at -56 (32,47). Cloning and sequence analysis of the trmA gene from S. typhimurium.…”
Section: Resultsmentioning
confidence: 99%
“…A sequence similar to the E. coli factor for inversion stimulation (FIS) binding site (22) was found at positions 299 to 308 between the -35 regions of the trmA and btuB promoters (7 of 9 bp). FIS binding sites have also been found in the rrn promoters and are centered there at about -71, i.e., somewhat further upstream than the putative FIS binding site in the trmA promoter, which is centered at -56 (32,47). Cloning and sequence analysis of the trmA gene from S. typhimurium.…”
Section: Resultsmentioning
confidence: 99%
“…It was recently shown that FIS protein binds to an upstream activating sequence present in stable RNA operons, thereby activating transcription from downstream promoters (37). We therefore tested whether a deletion mutation infis affects proU expression.…”
Section: Methodsmentioning
confidence: 99%
“…Whether this is just a coincidence or whether it points to a functional role of the DNA bend for efficient proU expression is unclear at present. Sequence distributions associated with DNA curvature upstream of a number of procaryotic promoters with upstream activation of transcription have been described (44), and the binding of accessory proteins such as FIS and IHF to sequences upstream of promoters is implied in the activation of transcription (37,54). Our results with afis mutant show that FIS does not play any role in proU expression.…”
Section: Methodsmentioning
confidence: 99%
“…However, it cannot be predicted if Fis binding might occlude or enhance binding of other proteins at the ␥ origin. Prebinding of Fis at its own promoter excludes RNA polymerase (1a), but Fis binding enhances RNA polymerase binding elsewhere (62,68).…”
Section: Discussionmentioning
confidence: 99%